Relations of Metacognitive Skills and Critical Thinking for Learning Outcomes of Cognitive Learning High School Students in Biology Learning with Reciprocal Teaching Strategy - A.G. Candra Wicaksono (Pascasarjana Universitas Negeri Malang (UM), 2014)
Hubungan Keterampilan Metakognitif dan Berpikir Kritis terhadap Hasil Belajar Kognitif Siswa SMA pada Pembelajaran Biologi dengan Strategi Reciprocal Teaching Abstract: The aim of this research was to investigate the relationship between metacognitive and critical thinking skill toward student cognitive achievement in biology learning used reciprocal teaching strategy. The participant were 31 science class students of public senior high school of Lawang and 32 science class students of PGRI school Lawang. The data obtained from this research was pretes and postest score of student’s metacognitive skill, critical thinking and cognitive achievement. The data then analized by multiple regression analysis. The result of this research showed that there was correlation between between meracognitive and critical thinking skill toward student cognitive achievement in biology learning used reciprocal teaching strategy.Key Words: metacognitive skill, critical thinking, cognitive achievement, reciprocal teaching strategy Abstrak: Penelitian ini bertujuan untuk mengungkap hubungan antara keterampilan metakognitif dan berpikir kritis terhadap hasil belajar kognitif siswa SMA dalam pembelajaran Biologi yang dibelajarkan dengan strategi reciprocal teaching. Penelitian ini melibatkan 31 siswa kelas XI IPA dari SMAN 1 Lawang dan 32 siswa kelas XI IPA dari SMA PGRI Lawang Kabupaten Malang. Data yang diambil dalam penelitian adalah data pretes dan postes keterampilan metakognitif, berpikir kritis dan hasil belajar beserta selisihnya. Data dianalisis menggunakan analisis regresi berganda. Hasil analisis menunjukkan ada hubungan antara keterampilan metakognitif dan berpikir kritis terhadap hasil belajar kognitif siswa dalam strategi reciprocal teaching. Kata kunci: hasil belajar kognitif, keterampilan metakognitif, berpikir kritis, reciprocal teaching